Market Integration Analysis of Cayenne Pepper in East Java Province - Vetty Seily Kurnia Dessy; Hery Toiba; Fahriyah (HABITAT, 2022)
Market integration research has often been used to evaluate agricultural products' marketing performance. However, the involvement of marketing agencies in chili marketing resulted in a relatively high price difference and impacted market integration. So it is essential to understand how the chili market integration as an effort to improve marketing efficiency and price control policies. The study analyzed the causality and market integration of cayenne pepper prices at the farmers' and retailers' levels in East Java Province. The study used weekly cayenne pepper price data at the farmers' and retailers' levels from 2016 - 2020. The secondary data was obtained from the Department of Industry and Trade of East Java Province. The analytical methods used in this study were Engle-Granger Causality analysis and Error Correction Model (ECM). The findings showed that retail prices caused the farmgate prices, but not the other way. However, the price of cayenne pepper at the farmer and retail level in East Java Province has been integrated. Therefore, this study showed that there needs to be an improvement in the farmers' institutional system to improve the farmers' bargaining position to reduce the power of the selling price control at the farmers' level by traders.